2021
DOI: 10.1038/s41467-021-22986-4
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary ancient DNA reveals a threat of warming-induced alpine habitat loss to Tibetan Plateau plant diversity

Abstract: Studies along elevational gradients worldwide usually find the highest plant taxa richness in mid-elevation forest belts. Hence, an increase in upper elevation diversity is expected in the course of warming-related treeline rise. Here, we use a time-series approach to infer past taxa richness from sedimentary ancient DNA from the south-eastern Tibetan Plateau over the last ~18,000 years. We find the highest total plant taxa richness during the cool phase after glacier retreat when the area contained extensive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 66 publications
0
38
0
1
Order By: Relevance
“…The collection of the environmental data is described in detail in Supplementary Information. The three lake cores—core 14‐OM‐02B from the Omoloy region in Siberia, core 16‐KP‐01‐L02_Long3 from Lake Ilirney in Siberia, and Lake Naleng core in China—investigated in this study were sampled during previous Russian‐German and Chinese‐German field trips. A chronology for the Lake Ilirney core is published in Andreev et al (2021): for lake 14‐OM‐02, see Liu et al (2021) and for Lake Naleng, see Kramer et al (2010). Coring, transportation, preservation, and subsampling of the core for ancient DNA are described in detail in Supplementary Information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The collection of the environmental data is described in detail in Supplementary Information. The three lake cores—core 14‐OM‐02B from the Omoloy region in Siberia, core 16‐KP‐01‐L02_Long3 from Lake Ilirney in Siberia, and Lake Naleng core in China—investigated in this study were sampled during previous Russian‐German and Chinese‐German field trips. A chronology for the Lake Ilirney core is published in Andreev et al (2021): for lake 14‐OM‐02, see Liu et al (2021) and for Lake Naleng, see Kramer et al (2010). Coring, transportation, preservation, and subsampling of the core for ancient DNA are described in detail in Supplementary Information.…”
Section: Methodsmentioning
confidence: 99%
“…DNA extraction of core samples was conducted with the same extraction kit. A detailed description of the metabarcoding pipeline to generate the plant DNA data of the core from Lake 14‐OM‐02B is described in Liu et al (2020), Lake Ilirney is summarized in Huang et al (2021), and Lake Naleng is described in Liu et al (2021).…”
Section: Methodsmentioning
confidence: 99%
“…(3) the response of organisms, from individual taxa to communities, to past environmental changes (Coolen et al 2013;Domaizon et al 2017;Schulte et al 2021;Liu et al 2021).…”
Section: Critical Transitions Have Been Documentedmentioning
confidence: 99%
“…Recent research studies showed ancient DNA preserved in Qinghai Lake sediments was used to reconstruct the temporal succession of plankton communities in the past 18,500 years (Li et al, 2016). Moreover, a time series approach to infer past taxa richness from sedimentary ancient DNA from the southeastern Tibetan Plateau revealed a threat of warming-induced alpine habitat loss to Tibetan Plateau plant diversity (Liu et al, 2021). Therefore, the characteristics of climate change, the understanding of the continuous acquisition of fine molecular-level organic components, and the recording of large-scale environmental regional changes in climate characteristics and other scientific issues could be answered with a combination of interpretation from microbiology study (Coolen et al, 2004;Cao et al, 2017;Han et al, 2017).…”
Section: Introductionmentioning
confidence: 99%